Spectrum of hematological disorders in bone marrow aspirate and biopsy at tertiary care hospital, Karachi - Arshad, Fatima; Sajjad, Mehwish; Mona, Anum; Kouser, Shaheen (International Journal of Endorsing Health Science Research, 2021)
Background: Bone marrow analysis is an invasive practice applicable to identifying, staging, and pursuing tumours. The present study aimed to determine the frequency of malignant hematological disorders using bone marrow aspirate and biopsy at Dr. Ishrat ul Ebad Khan Institute of Blood Diseases (DIEKIBD). Methodology: In this retrospective study, 756 patient records were examined for bone marrow analysis including both aspiration & biopsy, from January 2014 to December 2018. The posterior superior iliac crest was preferred for bone marrow sampling and aspiration was done with the help of a Salah bone marrow needle. Results: It was observed that about half of the bone marrow examinations, i.e. 362 (47%), were carried out for tumour staging. Of which 260 (71.8%) were not compromised by primary diseases, while 102 (28.17%) cases contained primary diseases. Among non-malignant hematological disorders, megaloblastic anemia and mixed deficiency anemia were the most frequent, i.e. 24 (3.1%) each. In comparison, chronic myeloid leukemia and chronic lymphocytic leukemia were the most prevalent malignant hematological disorders 42(5.5%) each. Conclusion: As per the study results, the pathological analysis of bone marrow via aspirate and trephine biopsy has comparatively more significant value in diagnosing and staging the malignant disorders than the non-malignant disorders.